2022
DOI: 10.2196/36734
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Framework for Mixed Reality–Based Control of Collaborative Robot: Development Study

Abstract: Background Applications of robotics in daily life are becoming essential by creating new possibilities in different fields, especially in the collaborative environment. The potentials of collaborative robots are tremendous as they can work in the same workspace as humans. A framework employing a top-notch technology for collaborative robots will surely be worthwhile for further research. Objective This study aims to present the development of a novel fr… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 39 publications
0
4
0
Order By: Relevance
“…One of the main benefits of the Robot Framework is its flexibility in test case creation, as it allows collaboration between technical and non-technical team members. The framework's keyword-driven approach promotes test case reusability, simplifying maintenance and scalability [51].…”
Section: Robot Frameworkmentioning
confidence: 99%
“…One of the main benefits of the Robot Framework is its flexibility in test case creation, as it allows collaboration between technical and non-technical team members. The framework's keyword-driven approach promotes test case reusability, simplifying maintenance and scalability [51].…”
Section: Robot Frameworkmentioning
confidence: 99%
“…Telerehabilitation offers the perfect balance of at-home solutions with the care of a professional. Telerehabilitation effectively provides the necessary exercise for patients [ 101 , 102 ]. Furthermore, in combination with VR or exercise games, telerehabilitation yielded high satisfaction from the patients who use the system [ 103 , 104 ].…”
Section: Therapy Strategies Of the Hand Rehabilitation Devicesmentioning
confidence: 99%
“…Ponomareva et al [30] demonstrated a system for teleoperated robots in medical scenarios, which included an augmented virtual environment and region-based convolutional neural network for identifying and positioning laboratory instruments. Finally, Shahria et al [31] explored AR-based teleoperation, Chan et al [32] used AR in shared manufacturing tasks, and Brizzi et al [33] focused on AR for embodiment where the robot perspective is reconstructed. AR has also been used in robot programming, the creation of training scenarios, and the development of physical artefacts, enabling the possibility of programming a robot in a workspace without its physical presence and simulating motions before their execution [34][35][36][37].…”
Section: Introductionmentioning
confidence: 99%
“…Finally, Shahria et al. [31] explored AR‐based teleoperation, Chan et al. [32] used AR in shared manufacturing tasks, and Brizzi et al.…”
Section: Introductionmentioning
confidence: 99%